ANALISIS PENGENDALIAN KUALITAS TERJADINYA CACAT PADA PROSES PRODUKSI ADJUSTER R KWB (Studi Kasus di PT. Dina Karya Pratama. (Cicadas-Bogor) - Indrani Dharmayanti; Ajeng Rahayu (Jurnal Manajemen Industri dan Logistik (JMIL), 2018)
This study aims to find out the production process of Adjuster R KWB (a part of automotive sparepart),  the defect analysis and causes in PT. Dina Karya Pratama. It is a manufacturing company engaged in metal industry, especially automotive,. Quality control analysis is done using statistical called seven tools consisting of check sheet, p control chart, pareto diagram, and cause  and effect diagram to answer those problems.  The results of analysis show that the production process is controlled by the average proportion of defects (0.0071283). The level of disability is dominated by screw jam (50%) and circle not symmetry (35%). The main factors causing the defect are the engine factor that has not been hot, the method factor and the inaccuracy of labor.